1993
DOI: 10.1073/pnas.90.19.8915
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor receptor expression during embryogenesis and tissue repair suggests a role in endothelial differentiation and blood vessel growth.

Abstract: Vascular end lgwt factor (VEGF) b a polyetide mitogen that mulats the growth of endotlil clsin vigro and promotesthe growth ofblood vess in vivo. We have recetly shown that the ths-like receptor tyrosne kinae (flt) Is a receptor for VEGF. Here we used in siu hybrdzation to show that, In adult mouse tissues, the pattern offltexp-esslon was consstent with lo t io n endothe . We also show thatfkwas expsed endothellum during neovacularizton of heai skin wounds and during eady vascular devdopment In mose embyos. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
215
0
9

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(233 citation statements)
references
References 30 publications
9
215
0
9
Order By: Relevance
“…This hypothesis is further substantiated by the observation that both VEGF receptors were expressed in the growing vasculature of the decidua (this study and Millauer et al, 1993) and by the presence of high affinity binding sites in blood vessels of the maternal decidua (Jakeman et al, 1993). Peters et al (1993) reported VEGFRlAlt-1 expression by in situ hybridization during the period from E9.5 to E12.5 when major vascular structures such as the heart and the dorsal aorta have already formed. Our results extend these observations and show that VEGFRl/flt-1 is already expressed during the emergence of the first endothelial cells and that most blood vessels and capillaries in the embryo co-expressed both VEGF receptors throughout vascular development.…”
Section: Discussionsupporting
confidence: 55%
“…This hypothesis is further substantiated by the observation that both VEGF receptors were expressed in the growing vasculature of the decidua (this study and Millauer et al, 1993) and by the presence of high affinity binding sites in blood vessels of the maternal decidua (Jakeman et al, 1993). Peters et al (1993) reported VEGFRlAlt-1 expression by in situ hybridization during the period from E9.5 to E12.5 when major vascular structures such as the heart and the dorsal aorta have already formed. Our results extend these observations and show that VEGFRl/flt-1 is already expressed during the emergence of the first endothelial cells and that most blood vessels and capillaries in the embryo co-expressed both VEGF receptors throughout vascular development.…”
Section: Discussionsupporting
confidence: 55%
“…Several reports demonstrate that flk-1 is expressed in bipotential progenitor cells that can give rise to vascular endothelial cells and blood cells (Millauer et al, 1993;Peters et al, 1993;Yamaguchi et al, 1993;Huber et al, 2004). The presence of circulating GFP-positive cells in the transgenic tadpoles may reflect the maintenance of GFP protein in cells derived from these progenitors.…”
Section: Gfp Transgene Expression Recapitulates Endogenous Flk-1 Exprmentioning
confidence: 99%
“…The receptor tyrosine kinase flk-1/ vegfr2/KDR-1 is expressed in the developing embryonic vasculature as well as bipotential hemangioblasts, cells that become either blood or endothelial cells (Millauer et al, 1993;Peters et al, 1993;Yamaguchi et al, 1993;Huber et al, 2004). Targeted deletion of flk-1 results in the failure of the vascular system to develop in mice, demonstrating an essential role for this receptor tyrosine kinase in this process (Shalaby et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Having demonstrated that murine 4T1 and human MDA-MB-231 tumour cells express NP-1 and endothelial cells (HU-VEC's) express both NP-1 and KDR, we studied the effect of anti-NP1 and anti-KDR peptides on apoptosis. HUVECs were used as a positive control as these are known to express Flt-1, KDR and NP-1 (Peters et al, 1993 Figure 3A, B and C, respectively). Anti-KDR peptide induced significant apoptosis of HUVECs relative to controls (14177% vs control, Po0.05) but had no effect on tumour cell apoptosis in murine and human tumour cells (4T1, 77.12720.82%; MDA-MB-231, 86.2475.61% vs control), consistent with the lack of expression of Flk-1/KDR in these cells.…”
Section: Vascular Endothelial Growth Factor Receptor Blockade Inducesmentioning
confidence: 99%